A Survey of the Performance of Atrium Glass Type on Annual Energy Consumption of Commercial Complexes in Cold, Arid Climate, (Case Study of Almas-e Shargh Commercial Complex in Mashhad) - Tabesh, Shaghayegh (International Journal of Psychosocial Rehabilitation, 2020)
The present study focuses on the type of interior window skylight in commercial complexes of Mashhad due to its importance in cooling, heating, lighting, ventilation and indoor temperature. Based on this importance, the current study simulates the most appropriate type of glass in commercial complexes with internal skylight using comparative research method and Designer Builder software. This paper is aimed to find the best type of glass to reduce energy consumption and increase natural light and comfort for the residents. For this purpose, at first, the studied building was simulated in the software and then in order to determine the optimum glass of skylights in commercial complexes, in terms of impact on cooling, heating, lighting, ventilation and temperature in Almas-e Shargh Complex of Mashhad,5 glass types were selected. Then, after simulating them in the interior lighting of the commercial complex in two states (heating, ventilation and air conditioning) off and on, it was found that in the Almas-e Shargh Complex of Mashhad, the ventilation system in the off mode performs better than the ventilation system at on mode. Also, in terms of glass type, thermochromic glass is the most suitable type of glass to reduce temperature, cooling energy consumption by 10%, and increase the natural light entry in commercial complexes in cold arid areas of Mashhad both in the on and off modes of ventilation system.